Therapeutic effects of compound hypertonic saline on rats with sepsis - Dong,Fang (2014)
Sepsis is one of the major causes of death and is the biggest obstacle preventing improvement of the success rate in curing critical illnesses. Currently, isotonic solutions are used in fluid resuscitation technique. Several studies have shown that hypertonic saline applied in hemorrhagic shock can rapidly increase the plasma osmotic pressure, facilitate the rapid return of interstitial fluid into the blood vessels, and restore the effective circulating blood volume. Here, we established a rat model of sepsis by using the cecal ligation and puncture approach. We found that intravenous injection of hypertonic saline dextran (7.5% NaCl/6% dextran) after cecal ligation and puncture can improve circulatory failure at the onset of sepsis. We found that the levels of tumor necrosis factor-α, interleukin-1β, interleukin-6 and intracellular adhesion molecule 1 levels in the lung tissue of cecal ligation and puncture rats treated with hypertonic saline dextran were significantly lower than the corresponding levels in the control group. We inferred that hypertonic saline dextran has a positive immunoregulatory effect and inhibits the overexpression of the inflammatory response in the treatment of sepsis. The percentage of neutrophils, lung myeloperoxidase activity, wet to dry weight ratio of lung tissues, histopathological changes in lung tissues, and indicators of arterial blood gas analysis was significantly better in the hypertonic saline dextran-treated group than in the other groups in this study. Hypertonic saline dextran-treated rats had significantly improved survival rates at 9 and 18 h compared to the control group. Our results suggest that hypertonic saline dextran plays a protective role in acute lung injury caused after cecal ligation and puncture. In conclusion, hypertonic/hyperoncotic solutions have beneficial therapeutic effects in the treatment of an animal model of sepsis.